ANALYSIS OF CRIMINAL RESPONSIBILITY CRIMINAL CONDITIONERS OF RAPE TRIAL AGAINST WOMEN (Study of Decision Number 223 / Pid.B / 2019 / PN.Sdn) - AGUS SULENRO (Muhammadiyah Law Review Journal, 2021)
The results of the study were the factors causing the perpetrator to commit the criminal act of attempted rape in Decision Number: 223 / Pid.B / 2019 / PN.Sdn caused by 2 factors, namely internal factors and external factors. Internal factors such as the closeness between the perpetrator and the victim, the role of the perpetrator, and the position of the victim, while external factors include the environment or conditions in which the crime is committed, then the perpetrator's intention, low educational factors, and factors of low moral and religious knowledge, accountability of the perpetrators rape in Decision Number: 223 / Pid.B / 2019 / PN.Sdn, which states that the Defendant Musmulyanto Bin Adenan has been legally and convincingly proven guilty of committing the crime of "attempted rape" as in the First indictment of the Public Prosecutor, imposing a sentence on the Defendant Musmulyanto Therefore, Bin Adenan is imprisoned for 7 (seven) years The author's suggestion is that the judge should be more sensitive to see what facts arise during the trial, so that the facts that arise give rise to the judge's conviction that the defendant can or cannot be convicted. In addition, in making a decision, it must also be able to provide an appropriate sentence for the defendant based on aggravating or mitigating factors so as to create justice in society.